العلاقة بين العوامل الجغرافية والجزيرة الحرارية في مدينة الكوفة - الكناني، نهاد خضير كاظم; الجبوري، زينب موجد حمزة (جامعة الكوفة - كلية التربية للبنات, 2022)
أظهرت كثير من الدراسات إن أحد المشاكل الرئيسية التي تواجه سكان المدن في الوقت الحالي هي وجود الجزيرة الحرارية التي تنتج بسبب عمليتي التحضر والتصنع المصاحب إلى ازدهار وتطور الحضارة، إذا سببت هاتان العمليتين العديد من المشاكل والظواهر المناخية، ومنها الاحتباس الحراري والنفايات الصناعية وتلوث الهواء الجوي فضلا عن الجزيرة الحرارية التي هي موضوع الدراسة. تتأثر الجزيرة الحرارية في مدينة الكوفة وتكونها وخصائصها بالعوامل الجغرافية السائدة فيها، ومن أجل التوصل إلى قوة ذلك التأثير سوف نقوم هنا بالكشف عن العلاقة بين الجزيرة الحرارية في المدينة وبين أهم تلك العوامل بالاعتماد على ما تم تسجيله في كل محور من محاور الدراسة الميدانية من درجات الحرارة وسرع الرياح والرطوبة النسبية ومن خلال استخدام معامل الارتباط ومعادلة الانحدار الخطي البسيط. Many studies have shown that one of the main problems facing urban residents at the present time is the existence of a heat island that results from the processes of urbanization and industrialization accompanying the prosperity and development of civilization, if these two processes cause many problems and climatic phenomena, including global warming, industrial waste and air pollution, as well as The heat island which is the subject of the study.The heat island in the city of Kufa and its formation and characteristics are affected by the geographical factors prevalent in it, and in order to reach the strength of that influence, we will here reveal the relationship between the heat island in the city and the most important of these factors based on what was recorded in each of the axes of the field study of temperatures Wind speed and relative humidity through the use of correlation coefficient and simple linear regression equation.
Keywords: المناخ العراقي -- التغيرات المناخية -- الإشعاع الحراري -- التلوث البيئي -- الكثافة السكانية